Comparison Of SF6 Dissociation Rate Due To Positive and Negative Coronas - Rudi Irawan (Institut Teknologi Bandung, 2002)
Measurements of SF6 dissociation rate due to 75 μA positive and negative coronas have been carried out using a mass spectrometer. The results show that the rates of SF6 degradation and by-product production due to a positive corona are significantly higher than those for a negative corona. The rates of degradation and production of SF6 and gaseous by-products are proportional to the charge transported by the corona.Both positive and negative coronas produce the same major gaseous by-products, SiF4, SO2F2 and SOF2.Besides gaseous by-products, coronas also produce solid by-products, metal fluorides. Due to the impact of high-energy electrons and F¯, the positive electrode is always more coated and damaged than the negative electrode.